Effects of Reforestation on the Structure and Diversity of Bacterial Communities in Subtropical Low Mountain Forest Soils - Lin, Yu-Te; Whitman, William B.; Coleman, David C.; Chiu, Chih-Yu (Frontiers in Microbiology, 2018)
Reforestation with different tree species could alter soil properties and in turn affect the bacterial community. However, the effects of long-term reforestation on bacterial community structure and diversity of subtropical forest soils are poorly understood. In the current study, we applied error-corrected bar-coded pyrosequencing to characterize the differences in the soil bacterial community in a low mountain, subtropical forest subjected to reforestation. The communities were sampled in the summer and winter from a native broadleaved forest (BROAD-Nat) and two adjacent coniferous plantations, a Calocedrus formosana forest of 80 years (CONIF-80) and a Cunninghamia konishii forest of 40 years (CONIF-40). The soil bacterial communities among three forest types were dominated by Acidobacteria and Alphaproteobacteria. The distribution of abundant genera among communities was different. Based on the Shannon diversity index, the bacterial alpha diversity of CONIF-40 community was significantly higher than that in the CONIF-80 and BROAD-Nat soils. In both of the coniferous plantations, the soil bacterial diversity in summer was also higher than that in winter. Distribution of some abundant phylogenetic groups, K-shuff and redundancy analysis of beta diversity among communities showed that the bacterial structure of three soil communities differed between two seasons. These results suggest that seasonal differences influence the diversity and structure of bacterial soil communities and that the communities remain different even after a long period of reforestation.